Optical properties of doped and undoped 9-armchair graphene nanoribbons [data]: optimized geometries for graphene nanoribbons with and without defects - Lindenthal, Sebastian; Fazzi, Daniele; Zorn, Nicolas; El Yumin, Abdurrahman Ali; Settele, Simon; Weidinger, Britta; Blasco, Eva; Zaumseil, Jana (Universität, 2023)
Graphene nanoribbons are one-dimensional stripes of graphene with width- and edge-structure-dependent electronic properties. They can be synthesized bottom-up to obtain precise ribbon geometries. Here we investigate the optical properties of solution-synthesized 9-armchair graphene nanoribbons (9-aGNRs) that are stabilized as dispersions in organic solvents and further fractioned by liquid cascade centrifugation (LCC). Absorption and photoluminescence spectroscopy reveal two near-infrared absorption and emission peaks whose ratios depend on the LCC fraction. Similarly, the Raman D/G-mode ratios vary with fraction and indicate a higher defect density for fractions obtained at higher centrifugal forces. Low-temperature single-nanoribbon photoluminescence spectra suggest the presence of two different nanoribbon species. Based on density functional theory (DFT) and time-dependent DFT calculations, pristine 9-aGNRs are assigned to the lowest energy transitions and 9-aGNRs with edge-defects, introduced by an incomplete graphitization, are assigned to more blue-shifted transition peaks. Hole doping of 9-aGNRs dispersion with the electron acceptor F4TCNQ leads to concentration dependent bleaching of the main absorption bands and redshifted, charge-induced absorption features but no new emission features, thus, indicating the formation of polarons instead of trions (charged excitons) in charged 9-aGNRs.